Hyper hemispheric lens applications in small and micro satellites. Issue 12 (15th December 2018) - Pernechele, Claudio; Dionisio, Cesare; Munari, Matteo; Opromolla, Roberto; Rufino, Giancarlo; Fasano, Giancarmine; Grassi, Michele; Pastore, Serena
Abstract: As well known, micro and nanosatellites are being proposed for a variety of space missions, due to the advantages offered in terms of flexibility, cost and development time-scales. They also allow the development of space missions based on distributed architectures, composed of a number of small platforms in coordinated flight. However, technological advancements are still needed to make micro and nanosatellite competitive with respect to larger platforms. In this paper, we explore the potentiality offered by hyper hemispheric lens for the development of miniaturized and multi-function sensors for use on board of micro satellites. Hyper hemispheric lens belong to the ultra-wide field-of-view optical objectives. Here a novel optics of this category is presented. Its field of view is 360° in azimuth (panoramic capabilities) and 135° for the off-boresight angle (hyper-hemispheric field). With such capabilities the lens may be exploited as a very-large field-of-view optics where moving parts can be avoided. This is of interest to space applications, in which devices with any moving part, representing a possible point of failure, shall be avoided or reduced to the minimum. A hyper hemispheric lens may, then, be adopted for electro optical devices in space satellite subsystems, such as star-, Sun- and Earth-sensors, or for monitoring the environment surrounding the satellite in the case of on-orbit servicing or active debris removal operations. Weight and cost budgets for small and micro satellites are also important parameters to determine their success. Hyper hemispheric lens may be kept quite compact in dimension and the need of a single imaging detector, for a so large field of view, strongly reduces costs. In this paper, we explore possible applications of a multi-purpose space device based on a hyper hemispheric lens on board of micro and nanosatellites.